Mouse Palmitoyl Protein Thioesterase: Gene Structure and Expression of cDNA - Salonen, Tarja (Cold Spring Harbor Laboratory Press, 1998)
Palmitoyl protein thioesterase (PPT) is the defective enzyme in infantile neuronal ceroid lipofuscinosis (INCL), which is a recessively inherited, progressive neurodegenerative disorder. We present here the cloning, chromosomal mapping, genomic structure, and the expression of the cDNA of mouse PPT. The mouse PPT gene spans >21 kb of genomic DNA and contains nine exons with a coding sequence of 918 bp. Fluorescence in situ hybridization to metaphase chromosomes localized the mouse PPT gene to the chromosome 4 conserved syntenic region with human chromosome 1p32 where the human PPT is located. PPT is expressed widely in a variety of mouse tissues. The mouse PPT cDNA is conserved highly with the human and rat PPT both at the nucleotide and amino acid sequence level. Transient expression of mouse PPT in COS-1 cells yielded a 38/36-kD differentially glycosylated polypeptide that was also secreted into culture media. Immunofluorescence analysis of transiently transfected HeLa cells indicated lysosomal localization of mouse PPT. Based on the high conservation of the gene and polypeptide structure as well as similar processing and intracellular localization, the function of PPT in mouse and human are likely to be very similar. [The sequence data described in this paper have been submitted to GenBank under accession no. AF071O25.]